Determination of different forms of aminothiols in red blood cells without washing erythrocytes. (17th October 2013) - Dellanoce, Cinzia; Cozzi, Lorena; Zuddas, Stefania; Pratali, Lorenza; Accinni, Roberto
ABSTRACT Detection and quantification of different aminothiols forms (reduced and total) in biological fluids are important for the investigation of oxidative stress‐related diseases and cell homeostasis study. The aim of this study was to optimize a HPLC method in order to determine both reduced and total thiol forms in red blood cells (RBC) at low temperature without washing erythrocytes. Analytical recoveries for total and reduced thiols were 91.6–98.5 and 94.9–98.2% respectively. The relative standard deviations intra‐assay for total and reduced thiols were 1.14–3.64 and 0.83–2.3% respectively and the relative standard deviations inter‐assay for total and reduced thiols were 1.12–3.54 and 0.84–2.03%, respectively. This method allows specific analysis of the aminothiol state inside the RBC, as a model of intracellular metabolism functioning. Copyright © 2013 John Wiley & Sons, Ltd.